PENGEMBANGAN MEDIA SCRAPBOOK PADA MATA PELAJARAN TEMATIK KELAS 3 TEMA 1 SUBTEMA 3 PERTUMBUHAN HEWAN DI SD ISLAM BAITUT TAQWA - Farah Fatimatuz Zahroh; Mohammad Afifulloh; Lia Nur Atiqoh Bela Dina (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
The development of scrapbook media with theme 1 sub-theme 3 animal growth at Baitut Taqwa Islamic Elementary School was made because this media is easy to operate by children and as a support during the learning process. This research is a research and development (Research and Development). The AADIE model (analyze, desaign, development, evaluation) is used in this study. The evaluation evaluation in this study involved 1 media expert with a total percentage of 62% so that the media was less feasible and less effective when used. The total percentage of 1 material expert gets 91%. The total percentage of 1 expert user (teacher) gets 97%. The total percentage of the result of individual trials involving 3 students got a total score of 97%. And lastly, the total average value of 11 students during the pre-test was 42 and at the time of the po-test the average value of students was 89 from the data, the scrapbook media was valid according to some experts, but scrapbook media still had many drawbacks. Finally, it needs to be revised again in order to perfect the scrapbook media product.. Keywords :Learning media, development, scrapbook